A Comparative Evaluation of Dental Erosion Caused by Tetrapacked and Aerated Beverages: An In-Vitro study - Haritha R.K; Sreeja.C; Samyukta S; Cyril Benedict.H; Nagaland.T; Sathish Muthukumar.R (Indian Journal of Forensic Medicine & Toxicology, 2022)
Introduction: Dental erosion is an evolving concern with the food market globalization. In a rapidlydeveloping nation as India, beverage consuming behavior has significantly increased. There is freeaccess to new foods and beverages even in the neighborhood grocery stores and they are perceived asmodern and healthy. Extrinsic erosion appears to be a growing problem as a result of overconsumptionof soft drinks or fruit juices or both. Materials and Methods: Freshly extracted premolars weretreated with H202 for 24 hours and weighed with ‘Essae FB-200’ with a readability of 0.001 gram. Thebeverages were grouped into 2 categories, 1- Natural or tetra-packed beverages, 2 - aerated beveragesand a control. 20ml of each beverage was taken and the pH was measured. The tooth was immersed ineach of the beverage and pH were noted 4th hourly for 48 hours accounting for sipping the beveragefor 5 minutes every day for 1.5 years. The weight of the tooth was rechecked after 48 hours. Results:The mean pre-treatment pH of category 1 was 5±1.33 and that of category 2 was 4.66±1.32. There isno significant difference in the mean loss of weight between the two groups (p-value 0.94) there is nosignificant difference in the mean change of pH between the two groups (p-value 0.26) Conclusion:The objective erosive liability of tetra-packed and aerated beverages on the dental enamel was foundto be similar. However, natural fruit juices showed nil to negligible objective signs of dental erosion.